The Use of Emoji for Communications Between Role-Players in Twitter: Semiotics Analysis - Bulan Rara Yangsen (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
A sign certainly has a meaning behind it, including the use of emojis. This allows someone to use an emoji to convey something. The meaning behind the use of these emojis can vary. Emoji are used in conversations between individuals and other individuals in an online conversation or in a network (online). The purpose of this research is to reveal the meaning behind the use of emojis used by role-players on Twitter. This research will discuss the delivery of certain meanings by an emoji to the recipient. The data from this study were taken from conversations between role-players on Twitter. This study uses an emoji semiotic approach with a qualitative descriptive method. The results of this study are the first use, emoji can visualize a person's emotions when exchanging messages through social media such as: (1) feelings of joy, (2) apologies and feelings of sadness, (3) satire, (4) support and praise, and (5) shame. Also, emojis are not used for a single situation or feeling. So, emoji can be used to express various kinds of feelings.